Designing A Household Waste ShredderMachine Using The Quality Function Deployment Method - Jakaria, Ribangun Bamban; Pradana, Fendy Nia (LPPM Institut Teknologi Adhi Tama Surabaya (ITATS), 2024)
Household waste, especially inorganic waste, is becoming an increasingly pressing challenge in waste management in the community, which can have a negative impact on the environment if not handled properly. This research aims to design a portable, effective, and efficient household waste shredding machine by developing essential attributes such as automatic, ergonomic, easy to operate, durable, safe to use, low cost, easy to disassemble, not easily damaged, and easy to move. The method used is Quality Function Deployment (QFD), which enables the identification and fulfilment of user expectations through in-depth analysis of the voice of the customer. The results showed that of the attributes developed, the most dominant attributes were safety in use and ease of operation, followed by portability and durability. Meanwhile, users considered attributes such as ease of disassembly and low cost less critical. The resulting machine design is able to fulfil all the criteria set by users. It provides an innovative solution to improve the efficiency of inorganic waste management at the household level to provide convenience, safety, and portability in its use. From the weighting of attribute values, the most dominant order to the last is the attribute of easy to move with a value of 10,542, easy to disassemble 9,404, safe when used 8,821, ergonomic 8,151, easy to operate 6,630, durable 6,248, low cost 5,439, the machine is not easily damaged 5,283, automatic 5,110.